Índices para que te quero: o bloco alfabetizador e sua implicação ao trabalho pedagógico - Adam, Anelise Gehrcke (2022)
The present study is linked to the Professional Master's Degree of the Federal University of Santa Maria (UFSM) of the Graduate Program in Public Policy and Educational Management. The research aimed to understand the implications of the literacy block in the ways of thinking and producing pedagogical work. To do so, it defined as specific objectives: identify the regulatory frameworks referring to the policies of the literacy block; recognize the evolution of the rates of approval and retention at the end of the literacy block of the state network in the period 2011-2019; build an informative material containing the rates of approval and retention at the end of the literacy block in the coverage of the 36th CRE; recognize the implications of continued progression to the literacy block in the pedagogical work. Studies by Dourado (2009), Freitas (2009), Gatti (2004), Jacomini (2010), Minayo (2002), Rodrigues (2018), as well as the Federal Constitution (1988), the Laws of Directives and Bases of National Education (1961, 1971, 1996), and the National Curricular Guidelines (2010) for the 9-year elementary school were references for analysis and problematization. From a quanti-qualitative approach, developed in two stages, the study included: survey and systematization of data on retention and approval of students in the coverage of the 36th CRE and organization of conversations, in the perspective of the ECER (Powaczuk et al., 2021) with the institution that had the highest average retention in the period investigated. The analysis of the quantitative indexes showed no great discrepancies between the institutions, demonstrating the homogenizing perspective of these indicators, since it annuls the contextual conditions from which the indexes emerge. Regarding the narratives from the conversations, the analysis was based on two categorical dimensions: extra-school and intra-school policies; and teachers' conceptions about learning in the school context, which unfolded into four recurrences: external policies and their discontinuities; internal school policies; vulnerable contexts and the school as a refuge for learning; and learning: external factors and their implications. It is concluded that the pedagogical work is based on teachers' conceptions which tension the applicability of educational policies, generating a production of meaning that is unique to each context. Therefore, we reach the thesis that for the generation of a consistent policy on the literacy block, it is imperative that there is training work, because it is necessary to reflect on the work developed in the school context, establishing moments of dialogue, problematizing, collectively projecting actions that will qualify the pedagogical work in the literacy block and, consequently, improve the indexes, growing the educational field as a whole.